PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KEPUASAN PELANGGAN PADA DEPARTEMEN BUBI (BIDANG USAHA BARANG INDUSTRI) PT. VARIA USAHA DI GRESIK - Elan, Umi; Kusmindah, Dina Harining (Fakultas Ekonomi Universitas Gresik, 2016)
The construction industry is an industry that continues to grow along with growth in the economy of a region . This condition can be seen by the increasing number of development . The quality of the resulting construction services must be improved in order to gain the trust and satisfaction of customers . Improving the quality of performance for services in the construction industry can be done by implementing a system of Total Quality Management.This study aims to identify and create a measurement instrument evaluation of the effects of the Total Quality Management of customer satisfaction at the department of Industrial Goods Business Field In PT Varia Usaha . By using 10 indicators , the authors tried to measure the performance of Total Quality Management ( TQM ) from the standpoint of customer satisfaction level will be the construction services.From the analysis and calculation of linear regression obtained R = 0.878 means quite high relationship between the independent variable with dependent variable X to Y is equal to 87.8 %, so it can be said the relationship variable X ( Total Quality Management ) on the dependent variable Y ( Customer Satisfaction ) is very high. And the results of the crosstab analysis showed that age and education have an influence on the Quality Obsession (X3) because it has an average rating of 2.63.